Effective H2 Separation through Electroless Pore-Plated Pd Membranes Containing Graphite Lead Barriers - David Martinez-Diaz; Raúl Sanz; Alicia Carrero; José Antonio Calles; David Alique (Membranes, 2020)
Hydrogen promotion as a clean energy vector could provide an efficient strategy for realizing real decarbonization of the current energy system. Purification steps are usually required in most H2-production processes, providing the use of Pd-based membranes, particularly those supported on porous stainless steel (PSS), important advantages against other alternatives. In this work, new composite membranes were prepared by modifying PSS supports with graphite, as an intermediate layer, before incorporating a palladium film by electroless pore-plating. Fully dense Pd layers were reached, with an estimated thickness of around 17 μm. Permeation measurements were carried out in two different modes: H2 permeation from the inner to the outer side of the membrane (in–out) and in the opposite way (out–in). H2 permeances between 3.24 × 10−4 and 4.33 × 10−4 mol m−2 s−1 Pa−0.5 with αH2/N2 ≥ 10,000 were reached at 350–450 °C when permeating from the outer to the inner surface. Despite a general linear trend between permeating H2 fluxes and pressures, the predicted intercept in (0,0) by the Sieverts’ law was missed due to the partial Pd infiltration inside the pores. H2-permeances progressively decreased up to around 33% for binary H2–N2 mixtures containing 40 vol% N2 due to concentration–polarization phenomena. Finally, the good performance of these membranes was maintained after reversing the direction of the permeate flux. This fact practically demonstrates an adequate mechanical resistance despite generating tensile stress on the Pd layer during operation, which is not accomplished in other Pd membranes.